TINJAUAN TENTANG PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS INQUIRY UNTUK PESERTA DIDIK KELAS VII SMP - Mirda Swetherly Nurva (STKIP ROKANIA, 2016)
This research used Plomp model which consist of three phases: preliminary research, prototipe phase, and assessment phase. In preliminary research phase, need and context analysis as well as review literatureswere done. In prototipe phase, lesson and plan an module based on done to determine the validity and practicality of the product. Validity of data analysis showed that the equipment of inquiry based learning was valid since the equipment of learning which was developed has already fulfilled the characteristics of validity both in the form of material and construct. In practical data analysis, it was known that the equipment of learning mathematics which was developed could be implemented well in learning mathematics activity